Evaluation of the vitamin D response index in a Saudi cohort - Shareefa A. AlGhamdi; Ranjini Ghosh Dastidar; Maciej Rybiński; Hadeil M. Alsufiani; Sawsan O. Khoja; Nusaibah N. Enaibsi; Safa F. Saif; Carsten Carlberg (Elsevier, 2024)
The concept of the vitamin D response index was developed based on vitamin D intervention studies conducted with Finnish cohorts. In this study, we challenged the concept by performing a single vitamin D3 bolus (80,000 IU) intervention with a cohort of 100 native Saudis. The change of serum levels of the proinflammatory cytokines interleukin 6, interleukin 8 and tumor necrosis factor measured directly before intervention in comparison to samples taken one and thirty days after vitamin D3 supplementation were used as biomarkers for distinguishing low, mid and high responders. Interestingly, we identified 39 % of the study participants as low responders. In contrast, when we used in a subset of 37 study participants whole blood expression changes of seven well-known vitamin D target genes one and thirty days after supplementation as alternative biomarkers, only 9 persons (24 %) were identified as low responders. In conclusion, in Saudi Arabia the rate of low vitamin D responders is equal or even higher than that in Finland. Therefore, similar to Nordic countries also in Saudi Arabia appropriate vitamin D3 supplementation is essential, in order to fulfill the needs of low responders.